PENGARUH MODEL READ-ANSWER-DISCUSS-EXPLAIN-CREATE (RADEC) UNTUK MENINGKATKAN KOMPETENSI MENULIS TEKS PROSEDUR PESERTA DIDIK KELAS V SEKOLAH DASAR - Puspita, Wulan; Siska Mega Diana; Nindy Profithasari; Frida Destini (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low competence of fifth-grade students in writing procedural texts in a coherent and systematic manner, and in accordance with linguistic rules. The purpose of this study was to determine the effect of the Read-Answer-Discuss-Explain-Create (RADEC) learning model on improving the procedural text writing competence of fifth-grade elementary school students. This study used a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The research population consisted of 48 students, and all of them were selected as the sample using the saturated sampling technique. Data were collected using a procedural text writing test and an observation sheet to assess the implementation of the learning process. Data analysis was carried out through prerequisite tests, including tests of normality, homogeneity, and linearity, followed by a simple linear regression test to examine the research hypothesis. The results of the analysis indicated that the Read-Answer-Discuss-Explain-Create (RADEC) model had a significant effect on improving the procedural text writing competence of fifth-grade elementary school students. Therefore, the RADEC model served as an effective alternative learning strategy for developing writing skills at the elementary school level.